Plyometric Training untuk Atlit dan Pelatih Cabang Olahraga Sepakbola Plyometric training for Athlete and Coach Football - Adityatama, Firman (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2022)
Football is a game that is dominated by lower extremity activities in every implementation of basic football techniques. The results of observations on football athletes, there are problems in doing long passes and shooting. Lack of power in both kicks so that the long pass kick is not on target while the shooting ball is easily caught by the goalkeeper. The purpose of this service is to provide insight to football coaches regarding plyometric training for leg muscle power training and how to apply plyometric training in athlete training programs. Service activities in the form of plyometric training for football coaches in Kuningan Regency were held on 11-12 September 2021. Data collection techniques in the form of field observations of football athletes' training and results of football coach training activities. The results of the service are carried out with: (1) providing material on the introduction of football in relation to leg muscle power, plyometric training and the principles of implementing plyometric training, as well as forms of plyometric training for football; (2) plyometric training practice.